Sosialisasi Teknologi Keamanan Digital: Strategi Menghindari Ancaman Siber bagi Pelajar Di SMPN 2 Tangerang Selatan - Eka Sri Rahayu; Ananda Masayu Lintang; Bayu Rayhan Sanjaya; Farhan Stiady Syah; Idpan Ashari; Kurnain Sofian; Meta Arfiola Suci; Rahmat Abdul Sahid; Ryan Dwi Irawan; Tanzilal Aziz; Firda Salsabila Putri (CV. Multi Kreasi Media, 2024)
An This community service activity in the field of digital security technology aims to raise awareness and understanding among middle school students about the importance of protecting themselves from cyber threats. In an increasingly digital world, cyberattacks have become a real threat that can damage personal data, steal important information, or even cause financial losses. Unfortunately, many students lack sufficient knowledge about preventive measures against cyberattacks, making them more vulnerable to such risks. Therefore, this activity aims to provide an understanding of how to avoid cyberattacks through socialization, training, and simulations that can be applied in daily life. The steps taught include using strong passwords, managing privacy settings on social media, being cautious of suspicious emails and links, as well as the importance of security tools like antivirus software and firewalls. It is expected that through this activity, middle school students will be able to reduce the risk of falling victim to cyberattacks and become more cautious in using digital technology. The expected outcome of this community service activity is to enhance students' knowledge and skills in safeguarding personal data, as well as positively impacting safer digital behaviors.